Potential Role of the Resident Mesenchymal Stem-Like Cells in Renal Fibrogenesis after Ureteral Obstruction - Yong-Hua Peng; Jie Xiao; Chen Yan; Lan Luo; Tao-Sheng Li (Stem Cells International)
The mechanisms of renal fibrogenesis after ureteral obstruction remain unclear. We tried to primarily expand mesenchymal stem cells from renal tissues and then investigated their role in fibrogenesis after ureteral obstruction. Unilateral ureteral obstruction was induced by ligating the left ureteral duct of adult C57BL/6 mice. We collected the kidneys for experiments at 2, 7, and 14 days after operation. Histological analysis showed obviously fibrotic changes in the left kidney at 7 days and further increased at 14 days after ureteral obstruction. To expand mesenchymal stem cells, we minced the renal tissues into small explants (about 1 mm3) and cultured onto 10 cm dishes. Interestingly, the outgrowth of cells was observed significantly earlier from the explants of the obstructed left kidney than that of the unobstructed right kidney. These expanded cells showed the potency of adipogenic, osteogenic, and chondrogenic differentiations and positively expressed with CD44 and partly expressed with CD90, CD105, and CD106, but negatively expressed with CD34, CD45, and FSP1, suggesting the phenotype of mesenchymal stem-like cells (MSLCs). The mouse fibrosis RT2 profiler PCR array showed that many genes were changed over 2-fold in the MSLCs expanded from both kidneys at 2, 7, and 14 days after operation. Interestingly, profibrotic genes were prevalently enhanced in the left kidney with ureteral obstruction. Histological analysis also showed obviously infiltration of inflammatory cells in the left kidney at 14 days after operation. Our data indicate the potential role of resident MSLCs in renal fibrogenesis after ureteral obstruction, but further experiments are required to understand the relevant mechanisms.